2017
DOI: 10.1590/1981-22562017020.160179
|View full text |Cite
|
Sign up to set email alerts
|

Subjective and psychological well-being among elderly participants of a University of the Third Age

Abstract: Objective: The present study aimed to analyze the distribution of measures of subjective and psychological well-being according to demographic criteria and length of participation in the program. Method: A cross sectional study using the following instruments was carried out: a sociodemographic questionnaire (age, gender, education, length of participation in University of the Third Age (U3A) and similar programs located in the city of São Paulo, Brazil; an Overall Life Satisfaction Scale; a Life Satisfacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
13

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 25 publications
1
19
0
13
Order By: Relevance
“…The presentation of diplomas or certificates of education is not required for the enrollment in workshops and lectures. As UNATI participants respond to calls made by the programs, in general, their profile is characteristic of an active and successful aging (9) .…”
Section: Design Place and Period Of The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The presentation of diplomas or certificates of education is not required for the enrollment in workshops and lectures. As UNATI participants respond to calls made by the programs, in general, their profile is characteristic of an active and successful aging (9) .…”
Section: Design Place and Period Of The Studymentioning
confidence: 99%
“…In general, individuals attending UnATI have characteristics of a successful and active aging (9) . The elderly who maintain their independence and self-determination, that is, the capacity to exercise their autonomy, should be considered healthy, even if they present one or more chronic diseases (3) .…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that elderly individuals with tri-generational arrangements were female, widowed and with a larger number of children. The engagement in these activities may be related to motivational and relational factors, since participation in social activities may increase the perception of the elderly individual's quality of life (Borges & Magalhães, 2011;Mantovani, Lucca, & Neri, 2016;Cachioni et al, 2017). However, there was no relationship between the household arrangement, age, education, mood, the mean MSME score, and BADL-and IADL-related difficulties, which may be associated with two factors: (1) when selecting the cognitively healthy individuals (50% of the sample), the most dependent ones could have been excluded and this factor could have generated a selection bias; (2) it is a sample of elderly individuals with a high prevalence of functional difficulties (50%) and less variability in relation to the sociodemographic variables investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Diversas áreas abordaram diferentes termos e designações ao estudar o BES, os quais, mesmo tendo alguma similaridade, não podem ser tratados como sinônimos (Andrews & Robinson, 1991;Campbell, Converse, & Rogers, 1976;George, 1981;Horley, 1984). O consenso entre os conceitos relacionados à temática ainda não ocorreu, embora há tempos venha sendo sugerido por pesquisadores (Diener, 1984 O BES é a área da ciência que visa compreender quais os critérios utilizados pelas pessoas para avaliar sua vida (Diener, 1996), pensando o que a torna boa e desejável (Albuquerque & Tróccoli, 2004;Cachioni et al, 2017). Pode ser denominado de outras formas como: felicidade, satisfação, estado de espírito e afeto positivo.…”
Section: Bem-estar Subjetivounclassified
“…Assim, considera-se que os indivíduos avaliam suas vidas a partir de aspirações e comparações com fatos ocorridos no passado, bem como utilizam outras pessoas como parâmetros e modelos ideais de satisfação (Michalos, 1985;Cachioni et al, 2017). Isto pode levar a certo grau de discrepância entre a condição atual e o padrão comparado, pela possibilidade de envolver uma comparação superior, o que resultará na diminuição da satisfação.…”
Section: Satisfação Geral Com a Vidaunclassified